2022
DOI: 10.1002/adhm.202202460
|View full text |Cite
|
Sign up to set email alerts
|

Nonlysosomal Route of mRNA Delivery and Combining with Epigenetic Regulation Optimized Antitumor Immunoprophylactic Efficacy

Abstract: Currently, mRNA-based tumor therapies are in full flow because in vitro-transcribed (IVT) mRNA has the potential to express tumor antigens to initiate the adaptive immune responses. However, the efficacy of such therapy relies heavily on the delivery system. Here, a pardaxin-modified liposome loaded with tumor antigen-encoding mRNA and adjuvant (2ʹ,3ʹ-cGAMP, (cyclic [G(2ʹ,5ʹ)pA(3ʹ,5ʹ)p])), termed P-Lipoplex-CDN is reported. Due to an nonlysosomal delivery route, the transfection efficiency on dendritic cells (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…DSPE-PEG-Man and DSPE-PEG-Par were synthesized by a coupled reaction of DSPE-PEG-NH 2 and mannopyranosylphenyl isothiocyanate or pardaxin peptide, as reported. Then, S protein- and CpG-loaded LIPO with or without APC (or) and ER targeting was then prepared, named S + CpG@Man-LIPO, S + CpG@Par-LIPO, S + CpG@PM-LIPO, and S + CpG@LIPO. Blank LIPO and PM-LIPO without loading drugs were prepared as a control.…”
Section: Resultsmentioning
confidence: 99%
“…DSPE-PEG-Man and DSPE-PEG-Par were synthesized by a coupled reaction of DSPE-PEG-NH 2 and mannopyranosylphenyl isothiocyanate or pardaxin peptide, as reported. Then, S protein- and CpG-loaded LIPO with or without APC (or) and ER targeting was then prepared, named S + CpG@Man-LIPO, S + CpG@Par-LIPO, S + CpG@PM-LIPO, and S + CpG@LIPO. Blank LIPO and PM-LIPO without loading drugs were prepared as a control.…”
Section: Resultsmentioning
confidence: 99%
“…In a study, Liu et al reported a combination therapeutic strategy that used decitabine in combination with pardaxin-modified liposomes loading with tumor antigenencoding mRNA and adjuvant (2′,3′-cGAMP) for in vitro transfection of DCs and preparation of mRNA-DC vaccines. 200 The results showed that such combination therapy improved mRNA transfection efficiency while enhancing the maturation of DCs, and the mRNA-DC-based tumor vaccines also showed amplified immune responses under low-dose mRNA administration. Importantly, mRNA-DC tumor vaccines in combination with decitabine sensitized the efficacy of mRNA-DC vaccines by restoring the expression of MHC-I in the tumor cells.…”
Section: Combination Therapymentioning
confidence: 98%
“…[150] Considering that the clin- ical efficacy of cancer vaccines based on pre-determined neoantigens is limited due to the lack of broadly expressed tumor antigens among cancer cells and the risk of immune escape in treatments targeting single antigens, autologous tumor cells are used for preparing individualized tumor vaccines for inducing polyclonal T cell responses. [151] Applying whole-cancer cells as cancer vaccines could help overcome the limitations of cancer vaccines based on several selected neoantigens. However, when applying whole-cancer cell as cancer vaccines, it is necessary to ensure that all cancer cells are nonviable.…”
Section: Cancer Vaccines Based On Bio-mineral Treated Whole Cancer Cellsmentioning
confidence: 99%
“…[ 150 ] Considering that the clinical efficacy of cancer vaccines based on pre‐determined neoantigens is limited due to the lack of broadly expressed tumor antigens among cancer cells and the risk of immune escape in treatments targeting single antigens, autologous tumor cells are used for preparing individualized tumor vaccines for inducing polyclonal T cell responses. [ 151 ]…”
Section: Cancer Vaccines Based On Whole Tumor Cell (Without Destroyin...mentioning
confidence: 99%